An evaluation of variation in pathology investigations and associated factors for adult patients presenting to emergency departments with chest pain: An observational study. Issue 3 (27th December 2018) - Wabe, Nasir; Dahm, Maria R.; Li, Ling; Lindeman, Robert; Eigenstetter, Alex; Westbrook, Johanna I.; Georgiou, Andrew
SUMMARY: Objective: To determine variation in pathology test ordering practices and identify associated factors for adult patients presenting to emergency departments (ED) with chest pain and subsequently admitted with ischaemic heart disease. Methods: A retrospective study across six hospital EDs in New South Wales, Australia. A total of 6769 patient presentations between January 2014 and December 2017 met the inclusion criteria. Ordered pathology tests were grouped into three categories based on Australasian College for Emergency Medicine and the Royal College of Pathologists of Australasia recommendations: category I (no restriction in ordering), category II (can be ordered after consulting a supervisor) and category III (not for routine ordering in ED). The primary outcome was the proportion of category III test ordering across study EDs. Factors associated with category III test ordering were identified using a logistic regression. Results: A total of 34 936 pathology tests were ordered: 65.6% (n = 22 932) were category I/II tests and 34.4% (n = 12 004) were category III tests. Five tests (Calcium Magnesium Phosphate, Coagulation Studies, Lipase, C‐reactive Protein and Blood Gas tests) accounted for 84.7% of all category III tests. The proportion of category III tests ordered varied by hospitals from 29.8% to 45.9%. The proportion of patients with at least one category III test was 76.3% (range across hospitals: 68.3%‐95.6%). Increasing age, presentation to an ED at night, and those in an imminently life‐threatening triage category were significantly associated with increased likelihood of category III test ordering. The proportion of category III tests decreased over time. EDs in medium and/or regional hospitals were more likely to order a category III test. Conclusion: Pathology investigations for patients presenting with chest pain varied significantly across EDs suggesting opportunities to improve standardisation of test ordering practices.